Preparation and characterization of ultrafine nanoparticles of Cu doped lithium tetraborate - Khalilzadeh, Nasrin; Saion, Elias; Mirabolghasemi, Hamed; Crouse, Karen Anne; Shaari, Abdul Halim; Hashim, Mansor (Elsevier, 2015)
This study details an innovative single-step thermal synthesis of nano-sized lithium tetraborate doped with 0.1 %wt copper and its characterization. The heating temperature for the synthesis of the nanoparticle material was optimized by variation between 200 and 850 °C. The optimum amount of polyvinyl pyrrolidone (PVP) the capping agent was determined to be 0.027 mol per 1 g LTB-Cu. The calcination time was 2 h. Characterization of the samples was carried out using Thermogravimetry Analysis (TGA), Derivative Thermogravimetry (DTG), Differential Scanning Calorimetry (DSC), Fourier Transform Infrared (FTIR) Spectroscopy, X-ray diffractometer (XRD), transmission electron microscopy (TEM) and Ultraviolet–Visible (UV–Vis) spectroscopy. The product was thermally stable above 450 °C. FTIR, XRD and TEM results confirmed the formation of pure nano-crystalline copper doped lithium tetraborate between 450 and 750 °C. The optical bandgap was estimated to be 5.02–6.05 eV in the presence of different amounts of PVP at various calcination temperatures.